Noticing for Equity in Written Work: Exploring One Teacher's Student Work Analysis Practices - Leshin, Miriam S. (Mathematical thinking and learning, 2025)
Attending to students' thinking and using it to inform instruction has been shown to be an effective and equitable teaching practice. Research on teachers' noticing of thinking conceptualizes noticing as a cognitive process, while work on noticing for equity treats noticing as culturally situated but primarily focuses on participation. Drawing on theories of noticing thinking and noticing for equity, I extend noticing for equity to students' written work. This article describes a case study of what and how one sixth grade math teacher noticed when analyzing her students' written work, as well as what connections existed between her pedagogical commitments and her noticing. Close examination of this teacher's student work analysis revealed that she (1) attended to the details of students' strategies with an inquiry stance, (2) contextualized their understandings through a dual lens on student and teacher, (3) interpreted understandings through a strengths-based lens, and (4) planned to respond by identifying a range of work to share with the class. Additionally, this teacher's pedagogical commitments and equity stance were embedded in much of her noticing. Findings suggest important theoretical intersections between noticing of thinking and noticing for equity.